PREPARATION OF THE SINGLE MODE PLANAR OPTICAL SPLITTER MODULES AND THEIR CHARACTERIZATIONS - Mien, Vu Doan; Nghiem, Vu Thi; Truong, Pham Van (ASEAN Journal on Science and Technology for Development, 2007)
Optical splitter modules have been prepared based on 1x8 single mode silica planar waveguide optical splitter chips with 250 µm spacing and v-groove fiber arrays for applications in fiber optic communications. We report the technology of precise optical coupling and packaging of the splitter modules and the measurements of the insertion loss (< 11 dB),  uniformity (< 0.80 dB) and polarization dependence loss (PLD < 0.10 dB) as well as the lateral profile and the image of the input and output lights for the wavelengths of 1310 nm and 1550 nm. The main characteristics of the prepared splitter modules are about the same for the commercial available products. The prepared modules have been tested for operation in the conditions of wide temperature range (5–80°C) and humidity range (50–98%) and no changes in the main characteristics were observed.